Effects of Formic Acid-Treated Shrimp Meal on Growth Performance and Nutrient Digestibility in Broilers - Mustanur Rahman; Katsuki Koh (The Journal of Poultry Science, 2016)
This study was conducted to know the effect of formic acid-treated shrimp meal as a protein source on growth performance, digestibilities, and nitrogen (N) retention for broilers. Shrimp meal (SM) was treated with 3% formic acid (w/v) at room temperature for 20 minutes, sun-dried, ground through a 1.0 mm mesh screen, and then ready to use as the treated SM (TSM). Forty-two male broiler chicks (8 d old, Ross 308) were randomly divided into 7 dietary groups (6 birds each), namely control diet, diets containing 5, 10, and 15% of SM, and diets containing 5, 10, and 15% of TSM and offered diets till 35 d old. Final body weight, body weight gain and feed intake decreased significantly with increasing levels of SM in diets. Feed conversion ratio also decreased with increasing levels of the SM (P<0.05). Similar trend was observed in the TSM group, but the adverse effects of the TSM were milder in comparison to the SM group (P<0.05). Dry matter digestibility tended to decrease (P<0.05) with increasing levels of the SM but unchanged with increasing level of the TSM. Availability of ash decreased with increasing levels of the SM and TSM in diets (P<0.05). Although N retention decreased (P<0.05) with increasing level of the SM and TSM in diets but the decreasing trend was milder in the TSM groups than the SM groups. Moreover, chitin digestibility was significantly greater in the TSM groups than the SM groups. In conclusion, broilers received diets containing the TSM showed better growth performance along with improved nutrient digestibility and N retention which suggests that formic acid-treated SM can be used as a potential protein source in broiler diets.